The role of circRNA polyribonucleotide nucleoside transferase 1 on Gestational Diabetes Mellitus: The role of circ-PNPT1 on GDM - Chen, Xiaolu; Huang, Jiaou; Peng, Yangying; Han, Yu; Wang, Xiaoyan; Tu, Chuanfa (Cellular and Molecular Biology, 2022)
This study aimed to focus on the mechanism of circRNA polyribonucleotide nucleoside transferase 1 (circ-PNPT1)-mediated miR-889-3p/PAK1 on gestational diabetes mellitus (GDM). Placental tissues from normal pregnancy and GDM patients were collected to detect the levels of circ-PNPT1, miR-889-3p, and PAK1. The high glucose-induced human trophoblast cells HTR-8/SVneo were adopted to stimulate the GDM model in vitro (HG group) and were transfected with lentivirus to silence circ-PNPT1 (si-circ-PNPT1 group) and mimic to overexpress miR-889-3p (miR-889-3p group). Cell proliferation, apoptosis, migration, and invasion were detected by CKK-8, flow cytometry, Transwell, and scratch assay, respectively. The results showed that the expressions of circ-PNPT1 and PAK1 in the GDM patients were up-regulated, and miR-889-3p was down-regulated (P< 0.05). Compared with cells in the control group, the circ-PNPT1 and PAK1 in the HG group were up-regulated, and miR-889-3p was down-regulated (P< 0.05). The cell proliferation, migration, and invasion abilities were weakened, and the apoptosis rate increased (P< 0.05). E-cadherin protein was elevated, and the N-cadherin and Vimentin decreased (P< 0.05). Compared with the HG group, the expressions of circ-PNPT1 and PAK1 in the other two groups decreased, and miR-889-3p increased (P< 0.05). The cell proliferation, migration, and invasion were enhanced, and the apoptosis rate decreased (P< 0.05). E-cadherin, N-cadherin, and Vimentin decreased (P< 0.05). There were targeted binding sites for miR-889-3p with circ-PNPT1 and PAK1, indicating circ-PNPT1 promoted HG-induced trophoblast dysfunction through the miR-889-3p/PAK1 axis.